Malaria and the red cell. - Weatherall, D; Miller, L; Baruch, D; Marsh, K; Doumbo, O; Casals-Pascual, C; Roberts, D (2002)
Because of the breakdown of malaria control programs, the constant emergence of drug resistant parasites, and, possibly, climatic changes malaria poses a major problem for the developing countries. In addition, because of the speed of international travel it is being seen with increasing frequency as an imported disease in non-tropical countries. This update explores recent information about the pathophysiology of the disease, its protean hematological manifestations, and how carrier frequencies for the common hemoglobin disorders have been maintained by relative resistance to the malarial parasite. In Section I, Dr. Louis Miller and colleagues consider recent information about the pathophysiology of malarial infection, including new information about interactions between the malarial parasite and vascular endothelium. In Section II, Dr. David Roberts discusses what is known about the complex interactions between red cell production and destruction that characterize the anemia of malaria, one of the commonest causes of anemia in tropical countries. In Section III, Dr. David Weatherall reviews recent studies on how the high gene frequencies of the thalassemias and hemoglobin variants have been maintained by heterozygote advantage against malaria and how malaria has shaped the genetic structure of human populations.